Pendidikan Multikultural Dalam Membentuk Karakter Pemuda Di Perguruan Tinggi - Arsyillah, Berlian Tahta; Muhid, Abdul (Al-Fikr: Jurnal Pendidikan Islam, 2020)
Ethnic diversity, religion, language, race, ethnicity, and culture make the State of Indonesia amulti-cultural country or commonly called multicultural. Often the diversity that occurs inIndonesia causes strife that often causes it, oppression, terror in the name of religion. Universitiesin Indonesia have a role in addressing these talks. Multicultural Multicultural CurriculumImplemented in Multicultural Basic Subjects and Master of Islamic Studies' PAI Study Programsat the Faculty of Islam. Therefore, researchers are interested in learning more about whichmulticultural education process is happening in tertiary institutions. By focusing on the mainresearch, researchers explore thoroughly the curriculum applied in tertiary institutions, fromthis learning process can improve the character of students generated after attending lectures. Thefindings produced, in the process of education in higher education institutions that applymulticultural education that complements the structured curriculum, and becomes a specialcurriculum about Multicultural curriculum implemented in multicultural basics courses and PAImaster study programs in the faculties of Islam can be changed. multicultural youth.